Axial-flux induction motors for electric vehicles - Dianati, Babak; Kahourzade, Solmaz; Mahmoudi, Amin (2019 IEEE Vehicle Power and Propulsion Conference, VPPC 2019 - Proceedings, 2019)
This paper presents design optimization of axial- flux induction motors (AFIMs) for electric vehicles. The approach is based on an analytical resolution of the Maxwellâ™s equations inside a set of subdomains. The analytical method is verified against 2D finite-element analysis. It allows detailed modelling and accurate steady-state performance prediction of AFIMs in a very short time (under 1sec), making possible evaluation of numerous design for the optimization. The optimization effortlessly simulates and predict the performance of various AFIM designs based on driving cycles and vehicle limitations. An optimization based on driving cycle of electric vehicles is studied through considering a driving cycle and designing minimum-mass AFIMs capable of fulfilling it. It is observed that driving-cycle based motor designs benefit from mass reduction and ensures the feasibility of all operating conditions.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Analytical modelling; Axial-flux induction motor; Driving cycle; Electric vehicle; Optimization